(untitled) (MIST International Journal of Science and Technology, 2025)
Reducing the amount of cement in construction has become a challenge in the 21st century. In this study, limestone powder (LSP) is adopted to partially replace cement at different weight percentages (5%, 10%, 15% and 20%). The influence of LSP on engineering properties such as workability, compressive strength, splitting tensile strength, flexural strength and toughness, water permeability, and surface resistivity is investigated to assess the acceptability of LSP blended concrete and to find the optimum replacement level considering these properties. At low replacement levels (5% and 10%), the mechanical and durability properties are improved due to the nucleation effect of LSP. Beyond 10% replacement, the dilution effect dominates which disadvantages the concrete. The workability linearly rises with the increase in the LSP content. The compressive and tensile strength does not vary much from the control specimen up to a 10% replacement level. The highest compressive and flexural strength is recorded for 10% LSP replacement. Toughness calculated from the beam load-deflection curve showed an increased value with increased LSP replacement. In comparison to the control specimens, 6.4% higher flexural strength and 90% higher toughness index are achieved for 10% LSP. An equation has been proposed using a machine learning approach to predict the tensile strength of LSP blended concrete with 87% accuracy. Water permeability and chloride ion penetrability are reduced for higher LSP content as LSP works as a filler and enhances pore structure. This study summarizes that 10% cement substitution with the LSP can be adopted for overall better mechanical and durability properties of concrete. MIJST, V. 13,December 2025: 1-13 https://doi.org/10.47981/j.mijst.13(02)2025.574(01-13)